2008
DOI: 10.1016/j.ultsonch.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Improved extraction of vegetable oils under high-intensity ultrasound and/or microwaves

Abstract: Ultrasound-assisted extraction (UAE) and microwave-assisted extraction (MAE) techniques have been employed as complementary techniques to extract oils from vegetable sources, viz, soybean germ and a cultivated marine microalga rich in docosahexaenoic acid (DHA). Ultrasound (US) devices developed by ourselves, working at several frequencies (19, 25, 40 and 300 kHz), were used for US-based protocols, while a multimode microwave (MW) oven (operating with both open and closed vessels) was used for MAE. Combined tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
220
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(230 citation statements)
references
References 25 publications
2
220
0
8
Order By: Relevance
“…These findings were in agreement with those reported by Luque-Garcia and Luque de Castro 21 for the influence of ultrasound on the fatty acids composition of oilseeds. Cravotto et al 22 found the content in polyunsaturated fatty acids of seaweed oil obtained under conventional and ultrasonic conditions did not differ significantly. Results would indicate that oxidation of P. khinjuk hull oil did not occur during extraction by ultrasound; these results were confirmed by quality analyses.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings were in agreement with those reported by Luque-Garcia and Luque de Castro 21 for the influence of ultrasound on the fatty acids composition of oilseeds. Cravotto et al 22 found the content in polyunsaturated fatty acids of seaweed oil obtained under conventional and ultrasonic conditions did not differ significantly. Results would indicate that oxidation of P. khinjuk hull oil did not occur during extraction by ultrasound; these results were confirmed by quality analyses.…”
Section: Resultsmentioning
confidence: 96%
“…These results noticeably similar to previous studies which reported that the fatty acid composition of oil extracted with UASE was comparable to other conventional methods. For instance, Cravotto et al 22 found that UASE produced a higher oil yield, but the FAME profiles of oil from UASE and Soxhlet extraction were almost comparable. Tocopherol and tocotrienol compounds of all extracted oil samples are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The application of this ultrasound-assisted method to microalgal biomass can improve extraction efficiencies by reducing the extraction times and increasing the oil recovery yields. The experiments that were performed by Cravotto et al (2008) with the microalgae Crypthecodinium cohnii showed cell disruption after applying ultrasonic pretreatment prior to Soxhlet extraction with n-hexane, resulting in an increase in the oil extraction yields from 4.8 to 25.9% compared to Soxhlet extraction without any pretreatment. Additionally, Ranjan et al (2010) compared the oil extraction yields from Scenedesmus sp.…”
Section: Ultrasonicationmentioning
confidence: 99%
“…When microwaves irradiate the interior of a cell, the oscillation of polar substances causes rapid heating, moisture evaporation and increasing pressure, which lead to cell rupture followed by the release of the cell contents. Cravotto et al (2008) applied organic solvent extraction with n-hexane and microwave-assisted solvent extraction (using the same solvent) to the microalgae Crypthecodinium cohnii, achieving oil recovery yields of 4.8 and 17.8%, respectively. Recently, Balasubramanian et al (2011) promoted the cell wall disruption of Scenedesmus obliquus using the microwaveassisted method for oil extraction.…”
Section: Microwavementioning
confidence: 99%
“…These include: (i) non-contact heating; (ii) rapid heating; (iii) selective heating; (iv) a quick start/stop facility; (v) a high level of safety and automation; and (vi) heating from inside the body of the material (i.e., energy conversion instead of heat transfer) [1,3]. All of these advantages have promoted research into the application of microwave heating to a wide range of different processes including waste and biomass valorization [4], material synthesis [5,6], metallurgy and mineral processing [3,7], catalysis [8], organic synthesis [9], environmental technology [7,10], biomass extraction [11], etc.…”
Section: Introductionmentioning
confidence: 99%